Analisis Pengaruh Perceived Compatibility, Individual Mobility. Dan Driver’s Factor Dari Attitude Towards Use Serta Implikasinya Pada Intention To Use: Telaah Pada Calon Pengguna Aplikasi Onesmile di BSD CIty - Shandra Kurniawati (Universitas Multimedia Nusantara, 2017)
The research problem is posed to determine the intention to use mobile application OneSmile in terms of perceived compatibility, individual mobility and factors of the driver's based on the attitude towards use that perceived ease of use and perceived usefulness. This study used descriptive design with non-probability sampling method in judgement sampling techniques. The theoretical model in this study was presented in six hypotheses to be tested using Structural Equation Model. The sample was 120 respondents who are residents BSD CITY aged between 26 and 45 years, have mobile banking, and used the internet at minimum from 1 to 3 hours per day. The collection of information is done by giving questionnaires directly to the respondents. The result showed that there is an influence between perceived ease of use and perceived usefulness, also the perceived usefulness and the attitude towards use of mobile application OneSmile. Furthermore, attitude towards the use and individual mobility has an impact on the intention to use mobile application OneSmile. The perceived ease of use, however, did not have an affect positively on the attitude towards the use of mobile application OneSmile. In addition, the perceived compatibility resulted that there was no a positive influence on the intention to use mobile application OneSmile. Keywords: Perceived Ease Of Use, Perceived Usefulness, Attitude Towards Use, Perceived Compatibility, Individual Mobility, Intention To Use, Mobile Application.